Gait analysis for individually tailored interdisciplinary interventions in children with cerebral palsy: a randomized controlled trial. (10th February 2019) - Rasmussen, Helle M; Pedersen, Niels W; Overgaard, Søren; Hansen, Lars K; Dunkhase‐Heinl, Ulrike; Petkov, Yanko; Engell, Vilhelm; Holsgaard‐Larsen, Anders
Abstract : Aim: To test the hypothesis that improvements in gait and function following individualized interdisciplinary interventions consisting of physical therapy, orthotics, spasticity management, and orthopaedic surgery using instrumented gait analysis are superior to 'usual care' in children with cerebral palsy (CP). Method: This was a prospective, single‐blind, parallel‐group, randomized controlled trial investigating the effectiveness of interventions based on the use of gait analysis. Primary outcome was gait (Gait Deviation Index) and secondary outcomes were walking and patient‐reported outcome measures of function, disability, and health‐related quality of life. Follow‐ups were done at 26 weeks (questionnaires) and at the primary end point of 52 weeks (all outcomes). Results: Sixty participants with CP (39 males, 21 females, mean age 6y 10mo, standard deviation 1y 3mo, range 5y–9y 1mo) in Gross Motor Function Classification System levels I or II, were randomized to interventions with or without gait analysis. No significant or clinically relevant between‐group differences in change scores of the primary or secondary outcomes were found. The recommended categories of interventions were dominated by non‐surgical interventions and were applied in 36% to 86% of the participants. Interpretation: Interventions using gait analysis were not superior to 'usual care' on gait, walking, or patient‐reported outcomes in a sample of relatively young and independently walking children with CP not expected to need surgery. What this paper adds: Gait analysis in children with cerebral palsy in Gross Motor Function Classification System levels I or II recommends interdisciplinary interventions. Compliance to interventions recommended after gait analysis was low. No statistically significant advantages were identified for the intervention group versus the control group. What this paper adds: Gait analysis in children with cerebral palsy in Gross Motor Function Classification System levels I or II recommends interdisciplinary interventions. Compliance to interventions recommended after gait analysis was low. No statistically significant advantages were identified for the intervention group versus the control group. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Análisis de marcha para la intervención interdisciplinaria adaptada individualmente en niños con parálisis cerebral: ensayo controlado randomizado: Objetivo: Comprobar la hipótesis que las mejoras en la marcha y la función luego de las intervenciones interdisciplinarias individualizadas de terapia física, ortésis, tratamiento antiespástico, y cirugía ortopédica son superiores que "tratamiento convencional" en parálisis cerebral (PC) utilizando un análisis de marcha instrumentada Metodo: Este fue un ensayo randomizado controlado, prospectivo, ciego, con grupo paralelo que investigó la efectividad de intervenciones basada en el uso de análisis de marcha. El resultado primario fue la marcha (Índice de Desviación de la Marcha) y los resultados secundarios fueron el paso y los resultados reportados por los pacientes de función, discapacidad y calidad de vida relacionada a la salud. Los seguimientos se realizaron a las 26 semanas (cuestionarios) y el punto de fin primario de 52 semanas (todos los resultados). Resultados: Sesenta participantes con PC (39 masculinos, 21 femeninos, edad media de 6 años 10 meses, desviación estándar de 1 años y 3 meses, rango 5 años 0 meses– 9 años y 1 mes) con niveles de GMFCS I o II, fueron asignados al azar intervenciones con y sin análisis de marcha. No se encontraron diferencias significativas o clínicamente relevantes entre los grupos en cuanto a los cambios de los resultados primarios y secundarios. Interpretacion: Las intervenciones que usaron análisis de marcha no fueron superiores al tratamiento convencional sobre el paso, la marcha o resultados reportados por los pacientes en una muestra de niños con PC relativamente jóvenes y de marcha independiente que no se espera que necesiten cirugía. Resumo: Análise de marcha para intervenções individualmente planejadas em crianças com paralisia cerebral: um ensaio controlado randomizado: Objetivo: Testar a hipótese de que melhoras na marcha e função após intervenções interdisciplinares individualizadas consistindo de fisioterapia, órteses, manejo da espasticidade, e cirurgia ortopédica usando análise de marcha instrumentalizada são superiors comparadas ao "cuidado usual" em crianças com paralisia cerebral (PC). Método: Este foi um estudo randomizado controlado prospectivo, único cego, com grupos paralelos, investigando a efetividade de intervenções baseadas no uso da análise de marcha. O desfecho primário foi a marcha (Índice de Desvio da Marcha) e os desfechos secundários foram o caminhar e medidas relatadas pelo paciente da função, incapacidade, e qualidade de vida relacionada à saúde. Acompanhamentos foram feitos com 26 semanas (questionários) e o encerramento primário foi 52 semanas (todos os resultados). Resultados: Sessenta participantes com PC (39 do sexo masculino, 21 do sexo feminino, média de idade 6a 10 m, desvio padrão 1a 3 m, variação 5a 0 m– 9a 1 m) nos níveis do Sistema de Classificação da Função Motora Grossa (GMFCS) I ou II foram fandomizados para intervenções com ou sem análise de marcha. Nenhuma diferença significativa ou clinicamente relevante entre grupos nos escores de mudança dos desfechos primários e secundários foram encontradas. As categorias de intervenção recomendadas foram dominadas pelas intervenções não‐cirúrgicas e foram aplicadas em 36% a 86% dos participantes. Interpretação: Intervenções usando análise de marcha não foram superiores ao "cuidado usual" para a marcha, o caminhar, ou resultados reportados por pacientes em ma amostra de crianças com PC relativamente jovens e com deambulação indepente, para a qual não se espera a necessidade de cirurgia.